Mangroves and Their Response to a Heavy Metal Polluted Wetland in The North Coast of Puerto Rico - Marixa Maldonado-Román; Johannys Jiménez-Collazo; Karlo Malavé-Llamas; Juan C. Musa-Wasil (Journal of Tropical Life Science, 2016)
Peninsula La Esperanza is part of the San Juan Bay Estuary and located in the north coast of Puerto Rico. Mangroves are the predominant type of vegetation; that can exhibit diverse external and internal mechanisms allowing them to tolerate and to act as phytoremediators of heavy metals (HM) in surrounding soils. This study was focused in three mangrove species that can be found in La Esperanza: Rhizophora mangle (RM), Laguncularia racemosa (LR) and Avicennia germinans (AG). Arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), lead (Pb), and zinc (Zn) were selected to be identified, measure concentrations in sediments, in green (GL) and senescent (SL) leaves, and study phytoremediation potential as a mitigation alternative calculating bioconcentration afctors (BCFs) and retranslocation percents (RT%). For this, Peninsula La Esperanza was divided in three main research sites. Our results show a significant difference among all heavy metals and their distribution in each site. Moreover, the mangrove species, A. germinans, showed lower RT% for Hg in all three sites, which could be considered the best species for phytoextraction of this heavy metal. The results suggest that the three species have a synergistic effect in the way they manage the heavy metal in surrounding polluted soils, although each species have a different capacity to manage each heavy metal.